2017
DOI: 10.1016/j.pec.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Group members’ questions shape participation in health counselling and health education

Abstract: Observing the occurrence of group members' questions helps group leaders to adjust their own actions accordingly and thus facilitate or guide group participation. Comparison of the type and frequency of members' questions is a way to detect different trajectories for delivering group interventions and can thus be used to develop methods for process evaluation of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Before focusing on the effect of VM on counseling interaction, we briefly show how overlap resolution takes place in face-to-face counseling. The group has been discussing a healthy diet (Extract from Logren et al, 2017aLogren et al, , p. 1837. N refers to the nutritionist, while A, B, and C are group members.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before focusing on the effect of VM on counseling interaction, we briefly show how overlap resolution takes place in face-to-face counseling. The group has been discussing a healthy diet (Extract from Logren et al, 2017aLogren et al, , p. 1837. N refers to the nutritionist, while A, B, and C are group members.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have described both ways in which professionals can encourage participation and how clients are able to initiate an active role in counseling encounters. For example, a counseling format that revolves around instructors' questions and clients' answers can limit client participation to merely answering questions in either individual or group counseling (Karhila et al, 2003;Logren et al, 2017aLogren et al, , 2017bPoskiparta et al, 1998Poskiparta et al, , 2001Tiitinen et al, 2018). Furthermore, Karhila et al (2003) have shown how direct presentation of troublesome issues in clients' lives invites discussion about their lifestyle while merely hinting at possible problems may invite only minimal participation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, second stories are considered to have a therapeutic effect. Our own previous studies have shown that sharing and addressing experiences is a central activity in group discussions, and that they are closely intertwined with practices of stance-taking (Logren et al, 2017a(Logren et al, , 2017bLogren, Ruusuvuori, & Laitinen, 2019)-that is, the ways in which participants in interaction evaluate the topics of talk, position themselves in relation to these topics, and align their positionings in relation to those of the other participants (Du Bois, 2007;Du Bois & Kärkkäinen, 2012).…”
Section: The Interactional Constraints and Resources Of Telling And Smentioning
confidence: 99%
“…In institutional group work, such as health promotion groups, talking about experiences is one of the central ways in which the objectives of the group are pursued (Borek & Abraham, 2018; Cormack, Jones, & Maltby, 2018; Due-Christensen, Zoffmann, Hommel, & Lau, 2012; Frigerio & Montali, 2016; Kennedy, Rogers, & Crossley, 2007; Logren, Ruusuvuori, & Laitinen, 2017a, 2017b; Lund, Argentzell, Leufstadius, Tjörnstrand, & Eklund, 2019; Mazanderani, Locock, & Powell, 2012; Öster, Hedestig, Johansson, Klingstedt, & Lindh, 2013; Patterson, Fleming, & Doig, 2019). Nevertheless, talking about experiences poses a practical dilemma for the participants: how to manage, on one hand, the uniqueness of an individual experience and, on the other hand, the accessibility, shareability, and comparability of experiences—and thus, how to address the claims participants make on the grounds of their experiences?…”
Section: Introductionmentioning
confidence: 99%